DIABETES MELLITUS TYPE 2 TREATMENT IN CHILDREN AND ADOLESCENTS: METFORMIN AS A FIRST AGENT OF CHOICE - T. L. Kuraeva ("Paediatrician" Publishers LLC, 2012)
In the past two years there has been seen a steady rise in diabetes mellitus type 2 sickness rate among youngsters. Thereby diabetes mellitus type 2 is no longer a problem exclusively of endocrinologists but also of pediatricians and pediatric endocrinologists. Diabetes mellitus type 2 that has several unique features if occurred in childhood. Also there are no therapeutical guidelines for this disease designed for treating children and adolescents, and that is why pediatric endocrinologists have to use guidelines for adult patients withdiabetes mellitus type 2. The article contains main stages and therapeutical methods of diabetes mellitus type 2 treatment, as well as reasonability of indications to start medicamental treatment.